Bullous Lupus Erythematosus Manifesting As Erythema Multiforme - Dhurat Rachita; Kamath Vishakha R; Jerajani Hemangi R; Shinde Santosh S; Gupta Madhuri T (Wolters Kluwer Medknow Publications, 2004)
Bullous SLE has a distinctive clinical, histopathologic and immunopathologic features that together constitute a unique bullous disease phenotype. We report a 33 year old female presenting with multiple tense vesicles and bullae on normal and erythematous skin over the body and oral erosions. Palms and extremities showed typical target lesions. She had consumed NSAIDs intermittently for joint pains. She was diagnosed as bullous erythema multiforme and started on oral prednisolone but lesions failed to heal. Patient recollected a history of low grade fever and a photosensitive rash in the past. Investigations revealed positive ANA with a peripheral pattern. A skin biopsy of a vesicle showed a subepidemal blisher. Perilesional direct immunofluorescence studies showed a linear deposition of IgG, IgA and fibrin along the basement membrane zone and perivascular deposition of IgG. Lapus band test showed a linear deposition of IgG, C3, IgM and fibrin at BMZ clinching the diagnosis of bullous lupus erythematosus.